Analisis Pendapatan Usaha Industri Pengolahan Kopi Bubuk Cap Jempol di Kabupaten Rejang Lebong - Tanti Novita; Nur Atika Fadilah; Novriza Wahyu Ardiansyah; Syamsir Hidayad (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2024)
This study aims to analyze the revenue and efficiency of the coffee powder processing industry "Cap Jempol" in Rejang Lebong Regency. The research employs a quantitative descriptive approach, focusing on revenue analysis, cost structure, and efficiency levels. Data were collected through interviews, observations, and questionnaires distributed to business owners and workers in the industry. The analysis shows that the total revenue (TR) of the "Cap Jempol" coffee powder business is IDR 35,000,000 per month, with total costs (TC) amounting to IDR 21.229.542 per month. The resulting profit is IDR 13.770.458 per month, and the Revenue-Cost Ratio (R/C Ratio) is calculated at 1.65, indicating that the business is profitable and efficient. Furthermore, labor productivity is measured at 100 kg per worker per month, demonstrating an efficient production process. Several factors influencing business revenue include raw material costs, operational expenses, market demand, marketing strategies, and competition. The findings suggest that improving production efficiency, expanding market reach, and optimizing cost management could enhance business profitability.